(untitled) (International Journal of Engineering and Computer Science, 2015)
TCP was designed to perform on wired networks, where packet loss is mostly caused by congestion, as compared to wireless networks, where losses due to error in channel are more likely. Hence TCP respond to all kind of losses by invoking congestion control and avoidance schemes resulting in performance degradation. In this thesis, a modified Loss Discrimination Algorithm is proposed which identifies the actual cause of packet loss and accordingly adaptively decreases the congestion window size in case of congestion loss and maintains the congestion window size in the case of wireless loss. Loss Differentiation Algorithms (LDA) are used to identify the actual cause of the packet loss so as to improve the performance of the wireless Network. This algorithm analyse the behaviour of Packet Inter-Arrival Time, ROTT (Relative One way Trip Time) and gives an idea of the cause of packet loss to the TCP. Experimental results validate the ability of our proposed algorithm to successfully classify the cause of the packet loss, with low End-to-End Delay and high packet delivery ratio. The Throughput is also better than before.